Gas6/TAM system as potential biomarker for multiple sclerosis prognosis - D’Onghia, Davide; Colangelo, Donato; Bellan, Mattia; Tonello, Stelvio; Puricelli, Chiara; Virgilio, Eleonora; Apostolo, Daria; Minisini, Rosalba; Ferreira, Luciana L.; Sozzi, Leonardo; Vincenzi, Federica; Cantello, Roberto; et al. (Frontiers in Immunology, 2024)
Introduction The protein growth arrest-specific 6 (Gas6) and its tyrosine kinase receptors Tyro-3, Axl, and Mer (TAM) are ubiquitous proteins involved in regulating inflammation and apoptotic body clearance. Multiple sclerosis (MS) is the most common inflammatory demyelinating disease of the central nervous system leading to progressive and irreversible disability if not diagnosed and treated promptly. Gas6 and TAM receptors have been associated with neuronal remyelination and stimulation of oligodendrocyte survival. However, few data are available regarding clinical correlation in MS patients. We aimed to evaluate soluble levels of these molecules in the cerebrospinal fluid (CSF) and serum at MS diagnosis and correlate them with short-term disease severity. Methods In a prospective cohort study, we enrolled 64 patients with a diagnosis of clinical isolated syndrome (CIS), radiological isolated syndrome (RIS) and relapsing–remitting (RR) MS according to the McDonald 2017 Criteria. Before any treatment initiation, we sampled the serum and CSF, and collected clinical data: disease course, presence of gadolinium-enhancing lesions, and expanded disability status score (EDSS). At the last clinical follow-up, we assessed EDSS and calculated MS severity score (MSSS) and age-related MS severity (ARMSS). Gas6 and TAM receptors were determined using an ELISA kit (R&D Systems) and compared to neurofilament (NFLs) levels evaluated with SimplePlex™ fluorescence-based immunoassay. Results At diagnosis, serum sAxl was higher in patients receiving none or low-efficacy disease-modifying treatments (DMTs) versus patients with high-efficacy DMTs (p = 0.04). Higher CSF Gas6 and serum sAXL were associated with an EDSS <3 at diagnosis (p = 0.04; p = 0.037). Serum Gas6 correlates to a lower MSSS (r2 = −0.32, p = 0.01). Serum and CSF NFLs were confirmed as disability biomarkers in our cohort according to EDSS (p = 0.005; p = 0.002) and MSSS (r2 = 0.27, p = 0.03; r2 = 0.39, p = 0.001). Results were corroborated using multivariate analysis. Conclusions Our data suggest a protective role of Gas6 and its receptors in patients with MS and suitable severity disease biomarkers.